Effect of Initial pH on the Microbial Growth, Final pH Value, Crude Protein and Ash Level of Agaricus bisporus Cap and Stem in Submerged Fermentation - Bahar Güngör; Şevket Özlü; Emrah Güngör; Aydın Altop; Güray Erener (Turkish Journal of Agriculture: Food Science and Technology)
The aim of the study was to investigate the effect of submerged fermentation with Lactobacillus spp. on the nutritional composition of Agaricus bisporus cap and stem. Fresh A. bisporus was provided, and the cap and stem parts were separated and cut into small pieces. Afterward, distilled water (400 ml) and urea (8.4 g) were added to the mushroom parts (100 g) and placed in different fermentation flasks. The fermentation flasks containing mushroom caps or stems were divided into two groups, and the pH levels of the fermentation medium were adjusted to 6 and 7. Fermentation flasks were autoclaved at 121°C for 15 minutes and Lactobacillus spp. was inoculated to each flask at 1 ml (108 CFU/ml). A positive control group was formed by allocating one uninoculated flask for each replicate of each pH value. Fermentation flasks were incubated for 48 hours at 30°C. After fermentation, fermented and inoculated mushroom cap and stem were analyzed to determine the crude protein, ash content, Lactobacillus spp. count and pH value. Lactobacillus spp. count was higher (P=0.028) in the pH 6 group of mushroom cap and tended to be higher (P=0.078) in the pH 6 group of mushroom stems compared with the pH 7 group. Submerged fermentation decreased (P<0.001) the ash content of the mushroom cap and stem in both pH values except the cap with pH 7 compared with the uninoculated mushroom. Similarly, the fermented mushroom cap and stem had lower (P<0.01) final pH values in both initial pH values. Lactobacillus spp. increased (P<0.001) the crude protein content of the mushroom cap with pH 6 but did not alter the crude protein content with pH 7. Besides, submerged fermentation decreased (P<0.001) the crude protein content of mushroom stem with both pH values. The results indicate that submerged fermentation using Lactobacillus spp. can be used to improve the nutritional composition of mushroom caps with pH 6.